2017
DOI: 10.1161/circgenetics.116.001631
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A/C -Related Cardiac Disease

Abstract: T he LMNA gene encodes for the intermediate filament proteins lamin A and C. LMNA mutations are associated with a wide spectrum of phenotypes ranging from progeroid syndromes, muscular disease, and lipodystrophy to isolated cardiac disease (dilated cardiomyopathy [DCM] and conduction disorders) and phenotypes consisting of combinations of these different features.1 Although their precise role is unknown, LMNA proteins are believed to play an important role in the structural integrity of the cell nucleus and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…In fact, mutation carriers shared a 1 Mb haplotype around the LMNA gene, with a combined LOD score of 3.46, suggesting a common founder. 12 The p.(Arg331Gln) mutation has been previously reported in 3 patients. One case was in Italy and was associated with late-onset DCM associated with conduction disease phenotype.…”
Section: Founder Mutations In the Lmna Genementioning
confidence: 97%
See 4 more Smart Citations
“…In fact, mutation carriers shared a 1 Mb haplotype around the LMNA gene, with a combined LOD score of 3.46, suggesting a common founder. 12 The p.(Arg331Gln) mutation has been previously reported in 3 patients. One case was in Italy and was associated with late-onset DCM associated with conduction disease phenotype.…”
Section: Founder Mutations In the Lmna Genementioning
confidence: 97%
“…The detection rate of genetic variants and mutations is faster than any functional study unraveling the functional role of each identified variant. Beyond in silico analysis that predicts, but does not demonstrate, the effects of the mutation/variant in the protein, immunohistochemical and electron microscopic studies of endomyocardial biopsy tissue may also uncover the effects of 13 Experimental studies, including in vitro studies of cellular models as reported by Hoorntje et al 12 or experimental animal models, 15 can help identify potential functional effects of each given variant. However, these studies may be time-consuming, expensive, and complex, and usually test 1 variant/mutation rather than the complex genetic makeup of each single patient.…”
Section: Effects Of Mutations In the Nextgeneration Sequencing Eramentioning
confidence: 99%
See 3 more Smart Citations